(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
The article examines the evolution of bilateral relations between Uzbekistan and the Philippines. Relying on a large number of previously unpublished archival materials, the author of this article attempted to analyze the main stages in the development of diplomatic cooperation between the two states. At the same time, the article provides information on the establishment of diplomatic relations between the two countries in 1992, as well as the factors that contributed both to the progress and to the regression of interstate cooperation.